House Dust Mite Aeroallergen Suppresses Leukocyte Phagocytosis and Netosis Initiated by Pneumococcal Lung Infection - Papanicolaou, Angelica; Wang, Hao; McQualter, Jonathan; Aloe, Christian; Selemidis, Stavros; Satzke, Catherine; Vlahos, Ross; Bozinovski, Steven (Frontiers in Pharmacology, 2022)
Asthmatics are highly susceptible to developing lower respiratory tract infections caused by Streptococcus pneumoniae (SPN, the pneumococcus). It has recently emerged that underlying allergic airway disease creates a lung microenvironment that is defective in controlling pneumococcal lung infections. In the present study, we examined how house dust mite (HDM) aeroallergen exposure altered immunity to acute pneumococcal lung infection. Alveolar macrophage (AM) isolated from HDM-exposed mice displayed a reduced phagocytic capacity to internalise SPN ex vivo and expressed alternatively activated macrophage (AAM) markers. In vivo, prior HDM exposure resulted in accumulation of AAMs in the lungs and 2-log higher bacterial titres in the BAL fluid of SPN-infected mice (Day 2). Acute pneumococcal infection further increased the expression of IL-10 and ARG1 in the lungs of HDM-exposed mice. Moreover, prior HDM exposure attenuated neutrophil extracellular traps (NETs) formation in the lungs and dsDNA levels in the BAL fluid of SPN-infected mice. In addition, HDM-SPN infected animals had significantly increased BAL fluid cellularity driven by an influx of macrophages/monocytes, neutrophils, and eosinophils. Increased lung inflammation and mucus production was also evident in HDM-sensitised mice following acute pneumococcal infection, which was associated with exacerbated airway hyperresponsiveness. Of note, PCV13 vaccination modestly reduced pneumococcal titres in the BAL fluid of HDM-exposed animals and did not prevent BAL inflammation. Our findings provide new insights on the relationship between pneumococcal lung infections and allergic airways disease, where defective AM phagocytosis and NETosis are implicated in increased susceptibility to pneumococcal infection.